Global mindset and its role in the international expansion of businesses in Costa Rica - Corrales Vargas, Jairol; León Darder, Fidel (Empresa y Sociedad, 2025)
Currently, there is limited research that delves into the analysis of the impact of global mindset on the internationalization dynamics of companies in emerging economies, particularly in the case of Costa Rica. This highlights the need to explore how the adoption of a global vision by business leaders and managers can positively influence the international expansion of companies, facilitating their integration into global markets. This study develops an analytical framework that rigorously quantifies and examines in detail the interrelationship between the adoption of a global perspective by managers and success in business internationalization within the Costa Rican context. A quantitative approach was adopted, with a sample of 266 managers from micro, small, medium, and large companies, and the multivariate Partial Least Squares Structural Equation Modeling (PLS-SEM) method was used for data analysis. The main finding confirmed the empirical evidence that global mindset is a determining factor in the internationalization of companies in Costa Rica.